Factors Associated with Mental Health Outcomes: Results from a Tertiary Referral Hospital in Lebanon during the COVID-19 Pandemic. Issue 1 (1st January 2021) - Msheik El Khoury, Fatima; Talih, Farid; Khatib, Mohamad F El; Abi Younes, Nadine; Siddik, Midhat; Siddik-Sayyid, Sahar
ABSTRACT: Coronavirus Disease (COVID-19) has caused global mental health impacts, and healthcare workers (HCWs) face an increased risk of exposure to the disease when compared to the general population. This study aimed to assess factors associated with mental health among Lebanese HCWs six months after the start of the COVID-19 pandemic. A cross-sectional study was conducted among HCWs at a tertiary hospital, in Lebanon between June and July 2020. The survey included data on demographics, exposure to COVID-19, preparedness to COVID-19 outbreak, risk perceptions of COVID-19, and mental health dimensions. Chi-squared and Fisher's exact tests were used to understand the association among these variables. One hundred and ninety-three of 1, 600 Lebanese HCWs participated. More than 80% reported high preparedness levels towards the COVID-19 outbreak, 69% believed that their job was putting them at risk, and 70% altruistically accepted these risks. Anxiety and depression symptomatology were present in 24% and 23% of HCWs; who were more likely to feel more stress at work (83% vs 60%; p = 0.004; 82% vs 61%; p = 0.01, respectively), feel afraid of falling ill (72% vs 55%; p = 0.03; 77% vs 54%; p = 0.01, respectively), fear death (21% vs 7%; p = 0.01; 25% vs 6%; p ≤ 0.001, respectively), and believed that people avoided their families (39% vs 21%; p = 0.01; 35% vs 65%; p = 0.02, respectively). HCWs who reported signs of depression were less likely to altruistically accept the risks of caring for COVID-19 patients, compared to those who did not (57% vs 74%; p = 0.03). This study aimed to detect factors associated with mental health among Lebanese HCWs during the COVID-19 pandemic. Findings suggested that altruistic acceptance of COVID-19 risks is higher among HCWs with positive exposure history to COVID-19 and those with less depressive symptomatology.